Perempuan sebagai Subjek Penafsir: Epistemologi Tafsir Feminis dalam Studi Al-Qur’an - Syakira Khofifa; Fauziah Amna Sipahutar; Farid Adnir (Yayasan Albahriah Jamiah Indonesia, 2026)
The centuries-long dominance of the tradition of Qur’anic interpretation, largely shaped by male experience, perspective, and scholarly authority, has given rise to debates regarding the representation of women in the production of exegetical knowledge and the legitimacy of women’s experiences as sources of religious meaning. This study aims to analyze women as interpretive subjects in feminist exegetical epistemology, explain the epistemological foundations that support this position, and identify the transformations it has brought about in contemporary Qur’anic studies. The method used is a qualitative approach grounded in literature review, combining the perspectives of exegetical epistemology and critical hermeneutics. Data were obtained from feminist exegetical literature and contemporary Qur’anic studies, then analyzed through content analysis and discourse analysis. The results of the study indicate that feminist exegetical epistemology critiques the construction of interpretive authority that tends to be masculine and reveals historical mechanisms that place women’s experiences outside the center of knowledge production. Through the reconstruction of sources, subjects, and interpretative processes, women’s experiences are affirmed as sources of knowledge that have equal epistemic legitimacy in understanding the Qur’anic text. This position affirms women as active epistemic subjects in the formation of meaning, broadens the horizon of interpretation, reexamines power relations within scientific authority, and encourages a more dialogical shift in the paradigm between text, interpreter, social context, and knowledge production. These findings affirm the contribution of feminist exegetical epistemology to the development of a more inclusive, reflective, and open methodology for Qur’anic studies, without neglecting academic principles and the scientific rules of exegesis.